Gender Differences in Sociademographic Characteristics and Risk Factors Among Condyloma Acuminata Patients in DR. Moewardi General Hospital Surakarta - Adniana Nareswari; Prasetyadi Mawardi; Arie Kusumawardhani; Endra Yustin Ellistasari (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2020)
Condyloma acuminata (CA) known as anogenital wart is the most frequent sexually transmitted infection worldwide. This highly infectious disease is caused by the human papilloma virus, whose its high reccurence rates contribute to direct medical costs, productivity loss and increased psychosocial impact. Thus, the prevention of this viral disease is more important than focusing on its treatment. This cross sectional retrospective study assesed the gender differences in sociodemographic characteristics and sexual risk factors of CA patients. There were 94 newly diagnosed CA patients, 47 males (50%) and 47 females (50%) during the period of January 2013- December 2017. The demographic data were taken from medical record and the additional data about the risk factors were from the questionnaires. Chi-square test was performed to compare between genders and p < 0.05 was considered statistically significant. There was significant difference between genders on all sociodemographic characteristics (age, occupation, education, marrital status) and risk factors (HIV/AIDS infection, condom using, age at the first sexual intercourse, number of lifetime sexual partner, type of intercourse) among CA patients. Our study revealed that male CA patients were mostly single, employed and multipartner, while CA female patients were mostly married, housewives and singlepartners.